THE IMPORTANCE OF CLINICAL PHARMACY AND PHARMACOKINETICS - Rahimov Bobir Sultanovich; Rahimova Dilorom Orifjonovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Clinical pharmacy and pharmacokinetics are important branches of modern medicine and pharmacy, which are aimed at understanding how drugs act in the human body and increasing their effectiveness and safety in clinical use. These disciplines are not limited to the scientific study of drugs, but also play an important role in solving complex issues that arise in their practical use. Thus, clinical pharmacy and  pharmacokinetics  are  closely  related  to  other  areas  of  medicine  and  serve  to maximize the effectiveness of drug therapy.